Lateral pressure effect on the ultimate strength of the stiffened plate subjected to combined loads. (1st November 2021) - Ma, Hongyang; Wang, Deyu
Abstract: As the basic unit of the ship bottom plate, the stiffened plate is usually subjected to multiple loads. Although the compressive loads may be responsible for the ultimate state of the hull structure, lateral pressure is also an essential component of loads for the bottom plate. In this paper, the collapse modes and ultimate strength of stiffened plates under the symmetric end condition subjected to combined axial compression and lateral loads are investigated to analyze the effect of lateral pressure. Results revealed that the lateral pressure could affect the ultimate strength and collapse mode by changing the pre-buckling strength and the magnitude of initial deflection. Correspondingly, the empirical formulas that contain the non-dimensional parameter of lateral pressure for calculating the ultimate strength are proposed to intuitively quantify the influence of lateral pressure. In addition, corresponding results obtained by experiments are compared with those obtained by empirical formulas and the validity of the empirical formulas was further verified. Highlights: The lateral pressure effect on the ultimate strength of stiffened plate subjected to combined loads has been systematically analyzed. Several empirical formulas of ultimate strength of stiffened plates under typical load conditions have been proposed, which could quantify the impact of lateral pressure on the ultimate strength. Non-dimension parameters of lateral pressure, the plate slenderness and the column slenderness has been included in the formulas. The validation of results have been verified by experimental results.